Causal associations of thyroid function and dysfunction with overall, breast and thyroid cancer: A two‐sample Mendelian randomization study. Issue 7 (3rd April 2020) - Yuan, Shuai; Kar, Siddhartha; Vithayathil, Mathew; Carter, Paul; Mason, Amy M.; Burgess, Stephen; Larsson, Susanna C.
Abstract : Whether thyroid dysfunction plays a causal role in the development of cancer remains inconclusive. We conducted a two‐sample Mendelian randomization study to investigate the associations between genetic predisposition to thyroid dysfunction and 22 site‐specific cancers. Single‐nucleotide polymorphisms associated with four traits of thyroid function were selected from a genome‐wide association meta‐analysis with up to 72, 167 European‐descent individuals. Summary‐level data for breast cancer and 21 other cancers were extracted from the Breast Cancer Association Consortium (122, 977 breast cancer cases and 105, 974 controls) and UK Biobank (367, 643 individuals). For breast cancer, a meta‐analysis was performed using data from both sources. Genetically predicted thyroid dysfunction was associated with breast cancer, with similar patterns of associations in the Breast Cancer Association Consortium and UK Biobank. The combined odds ratios of breast cancer were 0.94 (0.91–0.98; p = 0.007) per genetically predicted one standard deviation increase in TSH levels, 0.96 (0.91–1.00; p = 0.053) for genetic predisposition to hypothyroidism, 1.04 (1.01–1.07; p = 0.005) for genetic predisposition to hyperthyroidism and 1.07 (1.02–1.12; p = 0.003) per genetically predicted one standard deviation increase in free thyroxine levels. Genetically predicted TSH levels and hypothyroidism were inversely with thyroid cancer; the odds ratios were 0.47 (0.30–0.73; p = 0.001) and 0.70 (0.51–0.98; p = 0.038), respectively. Our study provides evidence of a causal association between thyroid dysfunction and breast cancer (mainly ER‐positive tumors) risk. The role of TSH and hypothyroidism for thyroid cancer and the associations between thyroid dysfunction and other cancers need further exploration. Abstract : What's new? Whether thyroid dysfunction plays a causal role in the development of cancer remains inconclusive. This two‐sample Mendelian randomization study investigated the associations between genetic predisposition to thyroid dysfunction and 22 site‐specific cancers. Evidence of a causal inverse association was found between thyroid‐stimulating hormone levels and overall cancer. Increased thyroid‐stimulating hormone levels and hypothyroidism were associated with decreased risk of thyroid and breast (mainly ER‐positive) cancer, whereas hyperthyroidism and increased free thyroxine levels were associated with a higher risk of breast (mainly ER‐positive) cancer. The results suggest that treatment of subclinical and diagnosed hyperthyroidism may be an efficient cancer prevention strategy.